Velcro-Like System Used to Fix a Protective Faecal Shield on Weevil Larvae - Skuhrovec, Jiří; Stejskal, Robert; Trnka, Filip; di Giulio, Andrea (PloS one, 2017)
The last instar larva and pupa of Eucoeliodes mirabilis (A. Villa & G. B. Villa, 1835) (Curculionidae: Ceutorhynchini) are described using drawings and SEM images and are compared and keyed with already described larvae of 58 other ceutorhynchinae taxa. The larval body has an effective combination of morphological adaptations that assist a unique biological defensive strategy. All larval stages of E. mirabilis feed ectophytically on leaves of Euonymus europaeus L. (Celastraceae), and the larval body is covered with a thick faecal shield. The fixation of this protective shield on the larval back is performed by a peculiar dorsal microsculpture composed of a dense carpet of microtrichia on the thorax and abdomen, which serves effectively as a velcro system. Because of this strategy, macrosetae on the larval and pupal body of E. mirabilis are completely reduced. Larvae of E. mirabilis also have distinct morphological adaptations for protecting the spiracles against intrusion of faeces and avoiding occlusion of the tracheal system: a) microtrichia around spiracles are slightly shorter, distinctly stronger and are arranged with high-density and in clusters and b) spiracles are protected by an external safety valve. This strategy of E. mirabilis larvae is unique, although somewhat similar to that of Criocerinae and Blepharida-group leave beetles (Galerucinae) (both Coleoptera: Chrysomelidae), but with distinctly different morphological adaptations.
Keywords: listy rostlin; Feces; Male; nosatcovití; Česká republika; Pupa; Adaptation, Physiological; mužské pohlaví; fyziologická adaptace; Celastraceae; Czech Republic; kukla; Weevils; larva; Animals; ženské pohlaví; zvířata; Plant Leaves; Larva; Female; feces